Real-life cohort experience after implementing HIV pre-exposure prophylaxis for one year in northwest Spain - Pérez-González, Alexandre; Represa, Marta; Coll, Pep; Potel, Carmen; Rodríguez-Rivero, Silvia; Flores, Erene V.; Vázquez-Estévez, Claudia; Ocampo, Antonio; Pousada, Guillermo; Poveda, Eva (Frontiers in Public Health, 2022)
Introduction Pre-exposure prophylaxis (PrEP) has become a useful tool to reduce the transmission of human immunodeficiency virus (HIV) in key populations. In this article we assessed the effectiveness, safety, adherence, sexually transmitted infections (STIs) dynamics, and frequency of anal dysplasia among a real-life cohort of PrEP users in Northwest Spain. Methods A retrospective cohort study was undertaken in the Alvaro-Cunqueiro Hospital, Vigo which included every individual who started daily emtricitabine/tenofovir-disoproxil-fumarate (FTC/TDF) between November-2019 and October-2021. Clinical and epidemiological data were obtained from the patient’s medical records. The effectiveness and safety of FTC/TDF were assessed by HIV serology and renal function monitoring every three months. Anal, urethral, and oropharyngeal exudates were collected quarterly after the baseline visit. Results A total of 126 individuals were considered eligible, most of the participants had previously been diagnosed with a STI (60.3%), 22% had consumed recreational drugs in the year prior, and 13% had engaged in chemsex. At the end of the follow-up, no cases of HIV infection were detected; 3 patients had discontinued FTC/TDF because of side effects but none of them had presented renal toxicity. In addition, the diagnosis of STIs during the follow-up was common (100 cases in 54 patients). Moreover, engagement in chemsex was more common within this latter group (22% vs. 6%, p = 0.013). Among the study population included in the anal screening programme, the frequency of dysplasia was 9%. Conclusions FTC/TDF was effective, safe, and tolerable in a real-life cohort; adherence remained high throughout the study period (79%). However, a high number of STIs were diagnosed, especially among patients who engaged in chemsex.